Exercise improves systemic metabolism in a monocrotaline model of pulmonary hypertension - Ganesha Poojary; Sampara Vasishta; R. Huban Thomas; Kapaettu Satyamoorthy; Ramachandran Padmakumar; Manjunath B. Joshi; Abraham Samuel Babu (Sports Medicine and Health Science)
Exercise training in pulmonary arterial hypertension (PAH) has been gaining popularity with guidelines now recommending it as an important adjunct to medical therapy. Despite improvements in function and quality of life, an understanding of metabolic changes and their mechanisms remain unexplored. The objective of this study was therefore to understand the metabolic basis of exercise in a monocrotaline model of PAH.24 male Wistar rats (age: 8–12 weeks and mean body weight: [262.16 ​± ​24.49] gms) were assigned to one of the four groups (i.e., Control, PAH, Exercise and PAH ​+ ​Exercise). The exercise groups participated in treadmill running at 13.3 ​m/min, five days a week for five weeks. Demographic and clinical characteristics were monitored regularly. Following the intervention, LC-MS based metabolomics were performed on blood samples from all groups at the end of five weeks. Metabolite profiling, peak identification, alignment and isotope annotation were also performed. Statistical inference was carried out using dimensionality reducing techniques and analysis of variance.Partial-least-squares discrimination analysis and variable importance in the projection scores showed that the model was reliable, and not over lifting. The analysis demonstrated significant perturbations to lipid and amino acid metabolism, arginine and homocysteine pathways, sphingolipid (p ​< ​0.05), glycerophospholipid (p ​< ​0.05) and nucleotide metabolism in PAH. Exercise, however, was seen to restore arginine (p ​< ​0.05) and homocysteine(p ​< ​0.000 1) levels which were independent effects, irrespective of PAH.Dysregulated arginine and homocysteine pathways are seen in PAH. Exercise restores these dysregulated pathways and could potentially impact severity and outcome in PAH.